Performance Of Regional Public Service Agencies: Accountability As A Moderating Variable - Yesi Mutia Basri; Mifta Hasanah; Vera Oktari (Politeknik Negeri Madiun, 2022)
This study aims to empirically examine the influence of leadership style and technology on the performance of the Regional Public Service Agency (RPSA) Health Center in Pekanbaru City. This study also examines Accountability moderation. This research was conducted using a survey method through a questionnaire. All RPSA Public Health Centers in Pekanbaru City were sampled in this study, with 140 RPSA managers as respondents. The results of data analysis using Moderated Regression Analysis (MRA) with SPSS show that leadership style and use of technology affect the performance of the RPSA Health Center. The results also show that accountability does not moderate the influence of leadership style on the performance of the PSA Public health center but moderates the effect of using technology on the performance of the RPSA Public health center. The results of this study contribute to improving the performance of health organizations, especially health centers in the city of Pekanbaru.